Math elementary school exam analysis based on the Rasch model - Herwin Herwin; Andi Tenriawaru; Abdoulaye Fane (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
This study aims to analyze the quality of mathematics exam tests in elementary schools using the Rasch model. This research is a type of descriptive quantitative research. The subject of this study were all items of School Examination Mathematical Questions in SDN Region III of Donri Donri Subdistrict, Soppeng Regency. The Mathematics Problem is 40 items. Besides that, in this study, 125 answer sheets from the participants were collected from 125 participants. The technique of data collection is done through documentation. This data collection technique is used to get a set of questions, answers, and a list of names of examinees. The data obtained were analyzed using the Rasch Model. The results showed that based on the Rash Model of 40 items on the mathematics exam 33 items (82.5%) were in a good category, while the other seven items (17.5%) were in a bad category. Test results indicate that the test information value is 13.8 on the ability scale -1.5 with a measurement error of 0.26.